Metronidazole Suspension for Paediatric Use in Developing Countries: Formulation, Quality, and Stability - Francesca Baratta; Chiara Zingarelli; Federica Fanton; Editson Lamy; Gaetano Di Lascio; Paola Brusa (Pharmaceutics)
Background/Objectives. The paediatric population is a heterogenous group that is known to be a therapeutic orphan despite the recent incentives to promote the development of children’s formulations. Especially in low and middle-income countries, there is still a worldwide shortfall for the treatment and prevention of a variety of paediatric conditions. In this context, we developed a formulation specifically intended to administer metronidazole to paediatric patients using basic and low-cost excipients and with a simple set-up method. Methods. Various mixtures of excipients were prepared to obtain a suitable metronidazole liquid formulation at a concentration of 250 mg/5 mL. The best formula was tested for its quality and stability, assessing the uniformity of content, the pH, and the dispersion quality. We evaluated the stability of the preparation for 180 days at room temperature (25 +/− 2 °C), in a thermostatic oven (40 +/− 2 °C), and in a fridge (4 +/− 2 °C). Results. The tests performed gave excellent results. No variation greater than 10% was detected in the metronidazole concentration or in pH values after 180 days regardless of the temperature conditions during storage. Moreover, the microscope analysis confirmed the absence of significant differences over time. Conclusions. The results were consistent in different environmental conditions, ensuring the possibility of using the formulation even in those tropical countries where is not always possible to guarantee the conservation of medicines in controlled conditions. Moreover, the simple composition and easy preparation procedure make it possible to produce the suspension in any context, ensuring the quality of the finished product.